The study method of palladium compound interaction with hydrogen on a carrier surface - A. S. Berenblyum; H. A. Al-Wadhaf (Тонкие химические технологии)
A method was developed to study the initial palladium compounds (e.g. acetate or chloride) interaction with molecular hydrogen on a carrier surface. It is based on absorption of the corresponding acid evolved in the course of the reaction and its quantitative determination. A special apparatus was created enabling to study the kinetics of such reactions. The method allows investigating the metal centers formation on a heterogeneous catalyst surface.